2019
DOI: 10.3390/pr7020110
|View full text |Cite
|
Sign up to set email alerts
|

A Composite Evaluation Model of Sustainable Manufacturing in Machining Process for Typical Machine Tools

Abstract: Machine tool is the basic manufacturing equipment in today's mechanical manufacturing industry. A considerable amount of energy and carbon emission are consumed in machining processes, the realization of sustainable manufacturing of machine tools have become an urgent problem to be solved in the field of industry and academia. Therefore, five types of machine tools were selected for the typical machining processes (turning, milling, planning, grinding and drilling). Then the model of the energy efficiency, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This is a systematic method which consists of simplified measurement of basic data and the calculation of the indexes from the data. [30] studied the green performance of CNC (Computer Numerical Control) machine tools. In this work, a model of energy efficiency, carbon efficiency, and green degree is established.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a systematic method which consists of simplified measurement of basic data and the calculation of the indexes from the data. [30] studied the green performance of CNC (Computer Numerical Control) machine tools. In this work, a model of energy efficiency, carbon efficiency, and green degree is established.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results show that energy saving can be realized by completing machining as early as possible on a machine tool, and taking advantage of machine flexibility. Lv et al [18] illustrate a composite evaluation method for sustainable manufacturing in a machining process for typical machine tools in terms of energy efficiency, carbon efficiency and green degree, by considering the theory and experimenting with a resource, energy and emission modeling method. They propose corresponding strategies for energy conservation and emission reduction.…”
Section: Manufacturing Engineering Issuesmentioning
confidence: 99%
“…The authors have claimed that the approach has encompassed all the major aspects of machining sustainability such as energy consumption, material consumption, service consumption, and generated waste. Lv et al have established energy efficiency, carbon efficiency, and green degree models with respect to the five kinds of metal cutting machine tools: turning, milling, grinding, planning, and drilling [16]. Following the models, the authors have suggested measures for energy conservation and emission reduction for these machine tools.…”
Section: Introductionmentioning
confidence: 99%